A Design of Compact Dual-Band Magnetoelectric Dipole Antenna - Zhang, Hao (International Journal of Mechanical and Electrical Engineering, 2024)
A compact dual-band magnetoelectric (ME) dipole antenna is proposed in this article. The antenna consists of two rectangular patches, two copper columns, and two substrates. The feeding is achieved through a bottom microstrip and rectangular slots, with the two symmetrical rectangular patches serving as electric dipoles and the two copper columns acting as magnetic dipoles. Electromagnetic simulations were conducted using Ansys HFSS, and the results indicate that the antenna achieves a return loss of less than -10 dB in the frequency ranges of 18.6-22.2 GHz and 27.7-32.1 GHz. The impedance bandwidths for the two bands are 17.8% and 14.8%, respectively. Two resonant points are observed at 19.1 GHz and 20.3 GHz in the low band, and at 28.8 GHz and 31.3 GHz in the high band. The realized gains are 4.3-5.2 dBi and 8.2-8.8 dBi respectively.